2013
DOI: 10.1039/c3gc41214h
|View full text |Cite
|
Sign up to set email alerts
|

THF co-solvent enhances hydrocarbon fuel precursor yields from lignocellulosic biomass

Abstract: A novel single phase co-solvent system using tetrahydrofuran (THF) promotes hydrolysis of maple wood to sugars, sugar dehydration, and lignin extraction simultaneously and achieves higher overall yields of the fuel precursors furfural, 5-hydroxymethylfurfural (HMF), and levulinic acid (LA) than previously reported from biomass. In a one-pot reaction, we obtained yields of 86% furfural, 21% HMF, and 40% LA in the liquid phase and over 90% extraction of lignin as a solid powder. The co-solvent reaction also prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
206
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(214 citation statements)
references
References 27 publications
8
206
0
Order By: Relevance
“…Cai et al obtained the highest published concentration of levulinic acid (4.8% with 75% yield) when treating maple wood that had been pretreated hydrothermally. 121 The importance of this prehydrolysis step was demonstrated again by Galletti et al…”
Section: 135mentioning
confidence: 89%
See 2 more Smart Citations
“…Cai et al obtained the highest published concentration of levulinic acid (4.8% with 75% yield) when treating maple wood that had been pretreated hydrothermally. 121 The importance of this prehydrolysis step was demonstrated again by Galletti et al…”
Section: 135mentioning
confidence: 89%
“…4 Other solvents, such as THF, can be used with similar results. Cai et al 121 reported the co-production of furfural and levulinic acid at 86% and 40% yield from maple wood, respectively, using THF-water as a solvent (3 : 1 ratio) at 443 K for 1 h using 1 wt% H 2 SO 4 . In addition, they reported the production of HMF at 21% yield (Tables 2-4).…”
Section: Simultaneous Production Of Furfural and Levulinic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, after the two-step hydrolysis the hydrolysate liquid contained a high yield of both furfural and levulinic acid. Compared with published relevant studies applying one-pot reactions (Alonso et al 2013b;Cai et al 2013), which resulted in either a high yield of furfural or a high yield of levulinic acid, a more balanced high yield of furfural and levulinic acid was obtained by this two-step method. In addition, according to previous reports, the hydrolysis efficiency of sulfuric acid and hydrochloric acid used as a catalyst may vary with the raw material (Herrera et al 2004;Meinita et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, organic solvents with low boiling points, that are easily recycled, and that are relatively non-toxic to environment, have received the most attention. THF is a typical low boiling point co-solvent applied in the generation of HMF, furfural, and levulinic acid from biomass conversion (Cai et al 2013(Cai et al , 2014. As a widely used industrial organic solvent, acetone also has a low boiling point and is easily recovered.…”
Section: Introductionmentioning
confidence: 99%